Synthesis, Characterization and Spectrophotometric Studies of New Hydrazone Derived from Ethyl benzoate - Sajid H. Guzar (Journal of Global Pharma Technology, 2016)
The present work includes synthesis and characteriation of new hydrazone derived from ethyl benzoate. Firstly, benzoate hydrazide [A] has been synthesized from the condensation of ethyl benzoate with hydrazine.Then the benzoate hydrazide was reacted with phenylisothiocynate to prepare [B]. Cyclization reaction of product [B] with sodium hydroxide produced terazole derivative [C].On the other hand, alcylation reaction of compound [C] with chloroethylacetate in the presence of Sodiumacetatetrihydrate as a catalyst resulted [D]. The acid hydrazide derivative [E] has been synthesized by the reaction of compound [D] with hydrazine hydrate . Finaly, hydrazone derived [M] was synthesized by the condensation reaction of the acid hydrazide [E] with 5-bromo-2-hydroxy benzaldehyde . The synthesized compounds were characterized by UV-Visible, FT-IR, 1H-NMR ,13C-NMR and Mass spectra. Analytical spectrophotometric study of the complexes of Lead (II),Cobalt(II) and Cadmium (II) with the hydrazone[M] was achieved. At a pH value of 7.0. lead, cadmium and cobalt salts reacted with [M] to form a 1:1 yellow, 1:1green, and 1:1 viole complexes with absorption peaks at 397, 389 ,and 396 nm, respectively. Under the optimal conditions, Beer’s law was obeyed over the ranges of 0.01- 0.000001 The apparent molar absorptivity and Sandell’s sensitivities were 8.5 ×102,8.0 ×103, and 9.8 ×102 L·mol−1·cm−1 respectively, and 0.00964, 0.00600, and 0.00275 µg·cm-2 respectively. The detection limits were found to be 32.75, 41.85, and 40.66 µg/mL-2 respectively.Keywords: Hydrazones Schiff base, Ethyl benzoate, Analytical studies. Introduction